Risk aversion in professionals of the financial sector - Dal Ross, Gabriel; Dala Nora, Bárbara; Milani, Bruno (Revista de Administração da UFSM, 2015)
The study of behavioral finance is essential to complement the modern theory of finance, as behavioral factors influence investment decisions. This study aimed to analyze the risk aversion of financial professionals, checking the differences between individuals that effectively invest their resources and those who would like to invest, still segregating the results according to gender, education, marital status, age, work time and number of dependents. The results are based on a survey, based on the methodology proposed by Kahneman and Tversky in 1979, applied to employees of eighteen agencies of four financial institutions in Santa Maria, Rio Grande do Sul. It was concluded that male respondents are more likely to risk and that the increase in the number of dependents increases risk aversion. It was noticed a highly risk averse profile, in which few respondents venture into investments that are not risk-free. Still, it was found that although there is the intention to make riskier investments, the respondents in fact do not, which can be linked to fear of reporting their mistakes.